Evaluation of groundwater availability to meet domestic water needs in Karangrejo Village, Petanahan District, Kebumen Regency - Dwi Kharisma Wijaya; Ananda Kris Setyaningsih; Annisa Anindita Sakiyo; Althafah Nur Fauziah; Danila Nur Rahmawati; Fayzal Burhan Aufal; Hafiz Firdaus; Marcelinus Pascalis Budi Setyawan; M. Hilal Alkahf Chams Saputra; Moudi Elviana; Wahyu Handayani; Wahyu Nur Hidayah; Tjahyo Nugroho Adji (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2026)
Groundwater plays a crucial role in fulfilling domestic water demands in Karangrejo Village, Petanahan District, Kebumen Regency. As the second-largest populated village in Petanahan in 2023 and bordered by the coastline, Karangrejo's groundwater availability is influenced by hydrogeological conditions. This study aims to determine groundwater flow patterns, assess water quality, estimate static and dynamic groundwater availability, and calculate domestic water demand. Methods used include groundwater level measurement, EM-VLF-VHF geophysical surveying, pumping tests, and domestic water-use assessment. The results show that groundwater flows from recharge zones in the central and partly northern areas toward discharge zones in the north and south. Groundwater availability reaches 5.54 billion L/year (static) and 362 million L/year (dynamic). Water quality indicates freshwater conditions based on temperature, electrical conductivity (EC), and Total Dissolved Solids (TDS) values. Domestic demand amounts to 98 million L/year, indicating a surplus condition. These findings demonstrate that the coastal aquifer in Karangrejo is capable of fulfilling local water demands and highlight the importance of aquifer characterization for sustainable groundwater management.